Prolonged Outbreak of Carbapenem and Colistin-Resistant Klebsiella pneumoniae at a Large Tertiary Hospital in Brazil - Rocha, Verônica França Diniz; Barbosa, Matheus Sales; Leal, Helena Ferreira; Silva, Giulyana Evelyn Oliveira; Sales, Nabila Monalisa Mendes Dantas; Monteiro, Adriano de Souza Santos; Azevedo, Jailton; Malheiros, Allan Roberto Xavier; Ataide, Ledilce Almeida; Moreira, Beatriz Meurer; Reis, Mitermayer Galvão; Bahia, Fabianna Márcia Maranhão; et al. (Frontiers in Microbiology, 2022)
Multidrug-resistant gram-negative bacteria, such as carbapenem and colistin-resistant Klebsiella pneumoniae (ColR-CRKP), represent a major problem for health systems worldwide and have high lethality. This study investigated the genetic relationship, antimicrobial susceptibility profile, and resistance mechanisms to ColR-CRKP isolates from patients infected/colonized in a tertiary hospital in Salvador, Bahia/Brazil. From September 2016 to January 2018, 46 patients (56 ColR-CRKP positive cultures) were enrolled in the investigation but clinical and demographic data were obtained from 31 patients. Most of them were men (67.7%) and elderly (median age of 62 years old), and the median Charlson score was 3. The main comorbidities were systemic arterial hypertension (38.7%), diabetes (32.2%), and cerebrovascular disease (25.8%). The average hospitalization stay until ColR-CRKP identification in days were 35.12. A total of 90.6% used mechanical ventilation and 93.7% used a central venous catheter. Of the 31 patients who had the data evaluated, 12 had ColR-CRKP infection, and seven died (58.4%). Previous use of polymyxins was identified in 32.2% of the cases, and carbapenems were identified in 70.9%. The minimum inhibitory concentration (MIC) for colistin was >16 μg/mL, with more than half of the isolates (55%) having a MIC of 256 μg/mL. The blaKPC gene was detected in 94.7% of the isolates, blaNDM in 16.0%, and blaGES in 1.7%. The blaOXA-48, blaVIM, and blaIMP genes were not detected. Changes in the mgrB gene were detected in 64.2%, and this gene was not detected in 8.9%. The mcr-1 test was negative in all 56 isolates. The PFGE profile showed a monoclonal profile in 84.7% of the isolates in different hospital sectors, with ST11 (CC-258) being the most frequent sequence type. This study presents a prolonged outbreak of ColR-CRKP in which 83.9% of the isolates belonged to the same cluster, and 67.6% of the patients evaluated had not used polymyxin, suggesting the possibility of cross-transmission of ColR-CRKP isolates. Alteration in the mgrB gene was detected in 64.2% of isolates.